(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: To see the results of neck dissection in thyroid carcinoma with metastatic cervical lymphadenopathy. Methods: This study was carried out in the Department of Otolaryngology at Bangabandhu Sheikh Mujib Medical University, Dhaka, for the period of two years from July 2006 to June 2008. Carcinoma thyroid patients with neck node were included in this study. Results: Mean age of the patients were 43.5 years. Mean follow up period was 15 months. In cases where radical or modified radical neck dissections were done no recurrence were found. Recurrences were found in 13.33% cases where selective neck dissections were done. Overall recurrence in anatomical neck dissection is 7.40% only. But in berry picking recurrence rate is 66.66% cases. So in berry picking locoregional control of disease is less satisfactory than anatomical neck dissection. Conclusion: In anatomical neck dissection locoregional control of disease is significantly more satisfactory than berry picking. Key words: Thyroid carcinoma; Papillary; Follicular; Medullary; Neck node metastasis. DOI: 10.3329/bjo.v16i2.6832 Bangladesh J Otorhinolaryngol 2010; 16(2): 80-85